Reasoning about Protocols using Dijkstra’s Calculus - Singh, Awadhesh Kumar (2004)
A mathematical model for the specification and verification of a data link layer protocol is proposed. The weakest precondition calculus, developed by Dijkstra, originally for sequential programs, has been chosen for this purpose. It is demonstrated that the wp-calculus provides a basis, not only for the modeling but also, for a straightforward and thorough analysis of large and complex distributed systems like data link layer protocol. This analysis contributes to the understanding of the system and could lead to an improvement in the design. The technique has been illustrated by describing the sliding window protocol.